Boxing the visual sphere: towards a systematic solution of the cubical perspective - Araújo, António (2019)
Cubic perspective is an attractive option for drawing VR panoramas, as it carries with it the familiarity of classical perspective and its ease of drawing line segments. Its simplicity is however only apparent as the transition of line images between the various planes of the cube can be baffling to the draughtsman. We argue that the best way to systematize this perspective is to see it fully as a spherical perspective and start by classifying and rendering its geodesics.